Development of Guided Inquiry Based Work Sheet with Class and Laboratory Activity on Chemical Bonding Topic in Senior High School - Zammiluni Zammiluni; Allizar Ulianas; Mawardi Mawardi (International Journal of Chemistry Education Research, 2018)
This research produced a teaching material in the form Work Sheet (LKPD) based guided inquiry which involves 3 levels of chemical phenomena namely macroscopic, sub-microscopic and symbolic. The worksheet was created using Plomp model and using guided inquiry learning cycle consisting of orientation, exploration, concept formation, application, and closure. This LKPD has been tested validity, practicality, and effectiveness. The validity test gives the result of the kappa moment of 0.83 with the category of very high. Analysis of practicality in one-to-one, small group, and field test stage showed the value of 0.80, 0.76, and 0.70 with all three values in the high category. Effectiveness test seen from student’s learning outcome before and after using LKPD obtained gain score is 0.76 in the high category and average activity of students is 86.3% at every meeting. The results showed that, worksheet using the Plomp model which has been produced are valid, practical, and effective Keywords: Guided inquiry, chemical bonding, validity, practicality, effectiveness